2016
DOI: 10.1111/crj.12509
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pleurodesis using different agents in management prolonged air leakage following lung resection

Abstract: Iodine pleurodesis can be considered as one of possible treatment methods of PAL after lung resection as it showed favorable results compared with Doxycycline pleurodesis or drainage alone regarding duration of air leakage, hospitalization and pneumothorax recurrence with only slightly increased pleural pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“… 16 There are also reports on acute respiratory distress syndrome after talc or OK-432 administration. 14 , 15 Moreover, another study showed that pleurodesis could induce acute exacerbation of IP, 17 which is why our institution avoids performing pleurodesis as much as possible among those with IP. Pleurodesis using an autologous blood patch had been reported to be safer and result in fewer complications than chemical pleurodesis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“… 16 There are also reports on acute respiratory distress syndrome after talc or OK-432 administration. 14 , 15 Moreover, another study showed that pleurodesis could induce acute exacerbation of IP, 17 which is why our institution avoids performing pleurodesis as much as possible among those with IP. Pleurodesis using an autologous blood patch had been reported to be safer and result in fewer complications than chemical pleurodesis.…”
Section: Discussionmentioning
confidence: 96%
“…16 There are also reports on acute respiratory distress syndrome after talc or OK-432 administration. 14,15 Moreover, another study showed that pleurodesis could induce acute A, Difference in the decline in the vital capacity (VC) between patients who used talc and those who did not use talc. Among patients who underwent pleurodesis, the decline in VC at 6 months postoperatively in patients who used talc and those who did not use talc were À12.9% AE 4.2% and À22.2% AE 2.8%, respectively (P ¼ .076).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several treatment options have been proposed for postoperative air leaks. Chemical pleurodesis with different agents such as talc, tetracyclines or iodine, prolonged chest tube drainage using a Heimlich valve system, insertion of endobronchial valves, or surgical intervention have been previously described 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…Chemical pleurodesis with different agents such as talc, tetracyclines or iodine, prolonged chest tube drainage using a Heimlich valve system, insertion of endobronchial valves, or surgical intervention have been previously described. [8][9][10] Autologous blood pleurodesis (ABP) was introduced 33 years ago as a treatment option in patients with pneumothorax. 11 Several theories have tried to explain the mechanism of action; one suggested that blood initiates an intrapleural inflammatory reaction leading to pleurodesis, while another theory supported the idea of the leaking airway being directly sealed by the blood.…”
Section: Introductionmentioning
confidence: 99%